1980
DOI: 10.1002/jso.2930140312
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the pancreas

Abstract: Epidermoid cancer of the pancreas is a rare variety of this malignancy. A case is presented. It has a characteristic angiographic appearance. Though in the past it has had a prognosis similar to the more common adenocarcinoma of the pancreas, a chemotherapeutic agent effective against epidermoid tumors at other sites has been effective in a case reported in the recent cancer treatment literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…It is our opinion that primary tumors of the pancreas that show any degree of definitive malignant squamous cell differentiation on routine sectioning should be considered adenosquamous carcinoma. Furthermore, it has been suggested in the medical literature that squamous cell carcinoma occurs de novo within the pancreas without an identifiable ductal component (16,(21)(22)(23). Based on our review of these publications, there was either limited diagnostic material or no resection specimen, or the cases were presented as part of a large series of pancreatic cancer, which did not specify the details of the individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is our opinion that primary tumors of the pancreas that show any degree of definitive malignant squamous cell differentiation on routine sectioning should be considered adenosquamous carcinoma. Furthermore, it has been suggested in the medical literature that squamous cell carcinoma occurs de novo within the pancreas without an identifiable ductal component (16,(21)(22)(23). Based on our review of these publications, there was either limited diagnostic material or no resection specimen, or the cases were presented as part of a large series of pancreatic cancer, which did not specify the details of the individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mikal and Campbell, as quoted by Sears et al, reported pancreatitis in 49 of 100 autopsied cases with pancreatic carcinoma, and Gambill, as quoted by Sears et al, showed significant pancreatitis by histologic criterion in 26 of 225 patients with pancreatic and ampullary carcinoma 1 . These pathology studies suggest that chronic pancreatitis may be associated with pancreatic carcinoma, but they could not specifically evaluate whether the malignant changes developed from the inflammatory lesions 1 .…”
Section: Figure 1 Hepatic Biopsy Showing Normal Liver In Lower Quadramentioning
confidence: 96%
“…A number of investigators have found that the combination of pancreatic calcification and chronic pancreatitis is associated with pancreatic cancer. Currently, no evidence supports a cause-effect relationship between pancreatitis and carcinoma 1 .…”
Section: Figure 1 Hepatic Biopsy Showing Normal Liver In Lower Quadramentioning
confidence: 99%
See 2 more Smart Citations